LincRNA Cox-2 Regulates Lipopolysaccharide-Induced Inflammatory Response of Human Peritoneal Mesothelial Cells via Modulating miR-21/NF-κB Axis - Yaoyao Bian; Lili Yang; Bin Zhang; Wen Li; Sen Wang; Shuling Jiang; Xi Chen; Wenlin Li; Li Zeng (Mediators of Inflammation)
Postoperative peritoneal adhesion (PPA) is a common postoperative complication caused by any peritoneal inflammatory process. This study aimed to identify the biological function of large intergenic non-coding RNAs (lincRNAs) Cox-2 in the inflammation reaction of adhesion formation. The Cox-2 expression in peritoneal adhesion tissues and normal tissues was detected. The human peritoneal mesothelium cells (HPMCs) were treated with lipopolysaccharide (LPS) to induce inflammatory injury. The effect of Cox-2 suppression on cell viability, apoptosis and inflammatory factors of LPS induced HPMCs injury were explored. The regulatory correlation between Cox-2 and miR-21, as well as the targeted genes of miR-21 were identified. Meanwhile, the regulatory mechanism of Cox-2/miR-21 axis on NF-κB pathway was explored. It indicated that Cox-2 was highly expressed in peritoneal adhesion tissues compared with that in normal tissues. Suppression of Cox-2 ameliorated LPS induced HMPCs injury as cell viability was promoted, and cell apoptosis and the production of inflammatory factors were inhibited. And suppression of Cox-2 reversed the LPS induced HPMCs injury by regulation of miR-21 negatively. miR-21 was negatively correlated with TLR4, and TLR4 was predicted as target gene of miR-21. Furthermore, the suppression of miR-21 on LPS induced HPMCs injury was reversed by knockdown of TLR4, which could inhibited the activation of NF-κB pathway axis. It suggested that the effect of Cox-2 on LPS induced HPMCs injury was achieved by negatively regulation of miR-21 and targeted TLR4 through NF-κB pathway axis. The findings may provide a new insight into preventing postoperative peritoneal adhesion.